A reference chromosomal map of the hot chili pepper Capsicum pubescens cv. “locoto” (Solanaceae) - Aguilera, Patricia Mabel (2021)
Capsicum pubescens is a cultivated hot chili pepper, consumed in Latin American cuisine as a distinctive ingredient, and popularly known as “locoto” or “rocoto”. This taxon is also an outstanding source of resistance to biotic and abiotic stresses as well as other valuable fruit traits for breeding of the worldwidely cultivated C. annuum and related species. In this study, the chromosome complement of C. pubescens cv. “locoto” (2n = 24) was deeply characterized through a sequential combination of conventional and molecular cytogenetics approaches comprising: Ag-NOR staining, heterochromatic fluorescent C-DAPI, DAPI/AMDCMA/DA bandings, fluorescence in situ hybridization (FISH) of Capsicum-derived probes of the 5S and 18S-25S rRNA genes and different regions of spacers of the ribosomal unit, as well as telomeric probe. The markers identified were systematically combined with morphological karyotype parameters - number, size, centromeres, satellites - to produce a physical map which allowed the identification of several landmarks in each individual chromosome. The reference chromosomal map of C. pubescens here presented is the most comprehensively developed in Capsicum so far. It is envisioned that this chromosomal map will serve as a reference framework for the upcoming sequencing projects and as starting point to assist future genetic mapping of important agronomic traits.